Design of horizontal stiffeners for stiffened steel plate walls in compression. (November 2018) - Xu, Zhaoyu; Tong, Genshu; Zhang, Lei
Abstract: The compressive stress is remarkable in design of steel plate walls (SPWs) for high-rise buildings. Stiffeners are required to avoid the compressive buckling in service limit state. This paper first studies the elastic stability of horizontally stiffened steel plate walls (S-SPWs) in compression. The effect of stiffener torsional stiffness on elastic buckling stress is presented. Then the study extends to the elastic-plastic stability of imperfect S-SPWs. Comparing the elastic and elastic-plastic behaviour, the increased ultimate compressive strength is smaller than the increased elastic buckling stress due to the column type buckling behaviour of wide plate. Stiffener torsional stiffness can also increase the ultimate capacity. Formulas to predict the stiffness requirement on horizontal stiffeners are proposed based on the philosophy similar to the stiffness requirement on brace for columns in compression. With some minor modifications, the proposed formulas show good accuracy compared with numerical results.